Organic waste as a sustainable feedstock for platform chemicals. (27th June 2017) - Coma, M.; Martinez-Hernandez, E.; Abeln, F.; Raikova, S.; Donnelly, J.; Arnot, T. C.; Allen, M. J.; Hong, D. D.; Chuck, C. J.
Abstract : Biorefineries have been established since the 1980s for biofuel production, and there has been a switch lately from first to second generation feedstocks in order to avoid the food versus fuel dilemma. To a lesser extent, many opportunities have been investigated for producing chemicals from biomass using by-products of the present biorefineries, simple waste streams. Current facilities apply intensive pre-treatments to deal with single substrate types such as carbohydrates. However, most organic streams such as municipal solid waste or algal blooms present a high complexity and variable mixture of molecules, which makes specific compound production and separation difficult. Here we focus on flexible anaerobic fermentation and hydrothermal processes that can treat complex biomass as a whole to obtain a range of products within an integrated biorefinery concept.